20.7k views
4 votes
Solve for 7(2c-1)-3=6+6c

User Hurcane
by
4.9k points

2 Answers

4 votes

Answer:

c = 2

Explanation:


7(2c-1)-3=6+6c\qquad\text{use the distributive property:}\ a(b+c)=ab+ac\\\\(7)(2c)+(7)(-1)-3=6+6c\\\\14c-7-3=6+6c\qquad\text{combine like terms}\\\\14c+(-7-3)=6+6c\\\\14c-10=6+6c\qquad\text{add 10 to both sides}\\\\14c-10+10=6+10+6c\\\\14c=16+6c\qquad\text{subtract}\ 6c\ \text{from both sides}\\\\14c-6c=16+6c-6c\\\\8c=16\qquad\text{divide both sides by 8}\\\\(8c)/(8)=(16)/(8)\\\\c=2

User Pedro Coelho
by
5.1k points
1 vote

Answer:

c=2

Explanation:

7(2c-1)-3=6+6c

14c-7-3=6+6c

14c-10=6+6c

14c-6c-10=6

8c-10=6

8c=6+10

8c=16

c=16/8

c=2

User Hintham
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.